PEMANFAATAN TONGKOL JAGUNG DAN CANGKANG BIJI KARET PADA PEMBUATAN BRIKET - Pakpahan, Hendra Swandi; Hamzah, Farida Hanum; Ayu, Dewi Fortuna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to get the best ratio between corncobs and rubber seed shells in making of charcoal briquettes. The study was carried out experimentally using a completely randomized design method which consisting of 5 treatments and 3 replications to obtain 15 experimental units. The treatments in the study were ratio of corncob charcoal and rubber seed shell charcoal as follows: P1 (90:10), P2 (80: 20), P3 (70 : 30), P4 (60: 40), and P5 (50: 50). The parameters observed in this study were water content, ash content, volatile matter content, bound carbon content, density, and calorific value. The results of variance showed that the percentage of corncobs and rubber seed shells gave a significant effect on water content, volatile matter content, and bound carbon content. Based on the results of the analysis, the best treatment in this study was P5 (50: 50), with 7.12% water content, 3.11% ash content, 17.25% evaporating content, 72.51% bound carbon content, and 0.42 g/cm3 density. Keywords: corncobs, rubber seed shells, briquettes